Processing and characterisation of polymer matrix composites using 3D printing - Goh, Choon Kiat (Nanyang Technological University, 2023)
The present paper studies existing joint configuration for carbon-fibre reinforced plastic (CFRP) scarf repairs from a previous experiment, B213[1], produced through additive manufacturing but utilizing two different adhesives. A total of three joint configurations were printed. With the scarf joint as the control, a step joint and a stagger joint were chosen for study. The adherends were printed with Onyx as the polymer and carbon-fibre being the reinforcement material. The adhesive DP460 and DP100 from 3M were used to bond the adherend joints together. The various joints were put under tensile loading for load & strain vs displacement measurements for comparison on a graph. In addition, a solid piece of CFRP was also included in the tensile test to compare the maximum tensile load before structural failure takes place and thus determine the joints efficiency. Analysing the results from the tensile test, the scarf joint and step joint experienced adhesive failure while the stagger joint showed adherend failure. Out of the three joint designs, the scarf joint displayed the best results followed by the stagger joint and finally the step joint.